Socialisation professionnelle des policiers : le rôle de l’école - Gorgeon, Catherine (Criminologie, 1996)
Anglo-Saxon studies on professional socialization of police officers have proven that the socialization process can be broken down into many steps, the major one being schooling. The results of all these studies have also demonstrated that the existence of specific cultural characteristics in the police profession influence and model new recruits. Recent French studies, with more quantitative methods, confirmed some of these results, but show many nuances and insist on the diversity in attitudes and expectations on the part of police students. It is namely the case with the year of training for constables.